efektivitas penggunaan media pembelajaran berbasis sparkol videoscribe terhadap kemampuan berpikir kreatif siswa smp muhammadiyah kupang - Mona, Bella Marselina; Zulfikar, Ryan Nizar; Rukman, Nia Kurniaty; Tefa, Defri (MEGA: Jurnal Pendidikan Matematika, 2024)
This comparative experiment with a quantitative approach study aimed to know the effectiveness of using Sparkol VideoScribe based learning media on the students’ creative thinking ability of Muhammadiyah Kupang Junior High School. The population were all seventh-grade students of SMP Muhammadiyah Kupang, while the samples were class VIIA as the control class and class VIIC as the experimental class. The cluster random sampling technique was used in this study. The data were analyzed based on the test results and using SPSS 23 software. The researcher also examined the hypothesis using the results of t test. The tcount value was 6.768 and the ttable for df 38 was 2.024, then 6.768> 2.024. So that, H0 was rejected and H1 was accepted. The hypothesis test at the 0.05 level with the t value df 38 obtained a sig value of 0.000 <0.05, then H0 was rejected and H1 was accepted. Thus, it can be concluded that there was an effect of using Sparkol VideoScribe-based learning media on the students' creative thinking skills.